Hospice Care and a Theology for Patients at the End of Life. (September 2014) - Tracy, Tara Flanagan
Abstract In Richard Kearney's text Anatheism, he claims that one can respond to the call of the stranger in two ways, with hospitality or with hostility. However, because the stranger possibly bears the presence of the divine, he urges one to risk responding to the stranger's call with hospitality rather than hostility, opening oneself up to encountering the sacred in the form of the stranger. In the present analysis, I claim that hospitality toward the stranger is modeled in the hospice philosophy of care for dying patients. I note the distinctions between the biomedical model of health care and the biopsychosoical model of care, and draw on Kearney's framework and Dorothee Soelle's text Suffering to suggest that, with regard to how to interpret pain, the act of hosting can be an option more viable than that of demonstrating hospitality.